The Relationship between Substance Abuse and Suicide among Adolescents - Darren Evans; Rima Tawk (University of North Florida, 2016)
Suicide, prominent in adolescents, presents a major public health problem. This study examined the relationship between substance abuse and suicide among adolescents after adjusting for socio-demographic, interpersonal violence, and mental health variables. Data were drawn from the Youth Risk Behavior Survey. Suicidal measures included ideation, plan, attempts, and severe attempts. Substance abuse, depression, purging, and forced sex were the major predictors. Our findings may be of value to educators, providers, and policymakers in helping to target teens contemplating suicide. To curb incidence of suicidal thoughts and behavior among teens, routine screenings for substance abuse in schools is recommended.